Identifying the Mass Rapid Transit (MRT) Customers Demographic and Traveling Pattern - Dullah H.; Khai W.J.; Ismail N.; Norhisham S.; Samsudin N.S.S.; Syamsir A.; Mohamad A.M.; Bakar M.F.A. (Springer Science and Business Media Deutschland GmbH, 2024)
As we know in modern era, the necessity for public transportation is becoming increasingly popular and preferable. The use of the MRT which is simple, easier, and inexpensive for all circles is the most common choice today. This study uses the convenience sampling of non-probability sampling technique. This is commonly used among students and researchers because less complicated, inexpensive, and easier to implement to the probability sampling research. Before make a research to this study, a pilot study was conducted with select randomly of 30 respondents as adapted from other study that is similar. The questionnaire is developed by using past literature reviews from other study that is similar papers on customers satisfaction, and it contains two main sections. The first section is about the demographicrespondents general data and travel behavior, such as gender, age, and occupation. The second section shows the data on customers travel pattern, such as the frequency of MRT use. For research methodology uses descriptive and cluster analysisage-based study. In order to perform statistical analyses, a descriptive analysis is important as a first step. It givesan overview of the distribution of the results. Based on the research gap regarding this topic, the Mass Rapid Transit (MRT) system in Malaysia is used as a case study to explore how customers age affects MRT service perceptions. A descriptive analysis was performed to achieve the first objective which is to identify respondents demographic and traveling patterns. These respondents have reasonable educational backgrounds, they are either currently under employment or could find jobs without much trouble. Their monthly incomes were mainly in the lower range where owning a private vehicle might not be financially viable. From the survey feedback on traveling patterns, most respondents use the MRT service Once in a while and mainly as a Preference. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.